2015
DOI: 10.1002/jrs.4747
|View full text |Cite
|
Sign up to set email alerts
|

Invoking forbidden modes in SnO2 nanoparticles using tip enhanced Raman spectroscopy

Abstract: forbidden modes and surface defect-related Raman features in SnO 2 nanostructures carry information about disorder and surface defects which strongly influence important technological applications like catalysis and sensing. Because of the weak intensities of these peaks, it is difficult to identify these features by using conventional Raman spectroscopy. Tip enhanced Raman spectroscopy (TERS) studies conducted on SnO 2 nanoparticles (NPs) of size 4 and 25 nm have offered significant insights of prevalent defe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 21 publications
5
57
1
Order By: Relevance
“…All the 2 %SnRuO samples have been analyzed by Raman, with the spectra displayed in Figure . Pure SnO 2 shows four Raman bands at about 475, 633, 690 and 774 cm −1 , which can be assigned in sequence to E g , A 1g , A 2u and B 2g vibration of rutile SnO 2 . The pure RuO 2 displays three typical Raman bands at 508, 626 and 690 cm −1 , which can be attributed in sequence to E g , A 1g and B 2g vibration of rutile RuO 2 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…All the 2 %SnRuO samples have been analyzed by Raman, with the spectra displayed in Figure . Pure SnO 2 shows four Raman bands at about 475, 633, 690 and 774 cm −1 , which can be assigned in sequence to E g , A 1g , A 2u and B 2g vibration of rutile SnO 2 . The pure RuO 2 displays three typical Raman bands at 508, 626 and 690 cm −1 , which can be attributed in sequence to E g , A 1g and B 2g vibration of rutile RuO 2 .…”
Section: Resultsmentioning
confidence: 95%
“…Pure SnO 2 shows four Raman bands at about 475, 633, 690 and 774 cm À 1 , which can be assigned in sequence to E g , A 1g , A 2u and B 2g vibration of rutile SnO 2 . [31] The pure RuO 2 displays three typical Raman bands at 508, 626 and 690 cm À 1 , which can be attributed in sequence to E g , A 1g and B 2g vibration of rutile RuO 2 . [32] In comparison with pure SnO 2 , a new Raman band at around 520 cm À 1 can be apparently observed for 2 %SnRuO-IMP and 2 %SnRuO-DP samples, which can be assigned to the E g vibration of RuO 2 .…”
Section: Xrd Hr-tem and N 2 -Bet Analysismentioning
confidence: 99%
“…S4 †). [47][48][49][50] The Raman spectrum change of the initial SnO 2 and SOC can also give valuable information about the particle size reduction. In initial SnO 2 , the Raman peak around 633 cm À1 can be assigned to A 1g vibration, and the peak around 471 cm À1 is due to E g vibration.…”
Section: Resultsmentioning
confidence: 99%
“…used TERS to invoke forbidden modes in SnO 2 nanoparticles. For quasi‐quantum dot sized 4‐nm nanoparticles, the TERS study was found to be the best technique to probe the finite size‐related Raman forbidden modes …”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…For quasi-quantum dot sized 4-nm nanoparticles, the TERS study was found to be the best technique to probe the finite sizerelated Raman forbidden modes. [34] Biosciences A principal area of growth in Raman spectroscopy is applications involving biological molecules and more recently biomedical systems. In this section, JRS papers with a central emphasis in the biosciences are described under the classifications of biomolecules, cells, bacteria and viruses, and biomedical applications.…”
Section: Theoretical Aspects Of Sers Enhancementmentioning
confidence: 99%